A Buthus martensii Karsch scorpion sting targets Nav1.7 in mice and mimics a phenotype of human chronic pain. Issue 2 (8th July 2021) - Lu, Wuguang; Cheng, Xiaoyang; Chen, Jiao; Wang, Mingyuan; Chen, Yonggen; Liu, Jinman; Sang, Ming; Zhao, Ningwei; Yan, Huaijiang; Cheng, Xiaolan; Zhou, Qian; Ye, Juan; et al.
Abstract : Supplemental Digital Content is Available in the Text. This study establishes Nav 1.7 as primarily responsible for Buthus martensii Karsch scorpion sting–evoked pain and sheds new insights into the development of Nav 1.7-selective modulators. Abstract: Gain-of-function and loss-of-function mutations in Nav 1.7 cause chronic pain and pain insensitivity, respectively. The preferential expression of Nav 1.7 in the peripheral nervous system and its role in human pain signaling make Nav 1.7 a promising target for next-generation pain therapeutics. However, pharmacological agents have not fully recapitulated these pain phenotypes, and because of the lack of subtype-selective molecular modulators, the role of Nav 1.7 in the perception of pain remains poorly understood. Scorpion venom is an excellent source of bioactive peptides that modulate various ion channels, including voltage-gated sodium (Nav ) channels. Here, we demonstrate that Buthus martensii Karsch scorpion venom (BV) elicits pain responses in mice through direct enhancement of Nav 1.7 activity and have identified Makatoxin-3, an α-like toxin, as a critical component for BV-mediated effects on Nav 1.7. Blocking other Nav subtypes did not eliminate BV-evoked pain responses, supporting the pivotal role of Nav 1.7 in BV-induced pain. Makatoxin-3 acts on the S3–S4 loop of voltage sensor domain IV (VSD4 ) of Nav 1.7, which causes a hyperpolarizing shift in the steady-state fast inactivation and impairs inactivation kinetics. We also determined the key residues and structure–function relationships for the toxin–channel interactions, which are distinct from those of other well-studied α toxins. This study not only reveals a new mechanism underlying BV-evoked pain but also enriches our knowledge of key structural elements of scorpion toxins that are pivotal for toxin–Nav 1.7 interactions, which facilitates the design of novel Nav 1.7 selective modulators.